Blockchain Adoption and Financial Reporting Quality in Indonesian Conventional Banks - Zakia Dewi; Trihatmaja Surya Prasetya; P. W. D. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), STIE Krakatau, 2026)
This study examines the effect of blockchain adoption on financial reporting quality among conventional banks listed on the Indonesia Stock Exchange (IDX) during 2022–2025, addressing the limited empirical evidence in the Indonesian banking context. Financial reporting quality was measured using Discretionary Accruals (DA) based on the Modified Jones Model, while blockchain adoption was measured using a binary dummy variable from annual and sustainability report disclosures. Panel regression analysis was conducted on 43 banks with 171 valid bank-year observations, with model selection based on the Chow and Lagrange Multiplier tests. Only three banks (BBNI, BBRI, and BNLI) disclosed blockchain adoption. The Common Effect Model was selected as the appropriate estimator. Blockchain adoption showed a negative coefficient, consistent with the hypothesis, but the effect was statistically insignificant (one-tailed p = 0.1089; R² = 0.90%). The hypothesis was not statistically supported. However, the directionally consistent result suggests that the insignificant finding may be attributed to limited statistical power due to the small number of adopters rather than the absence of an effect. The study is limited by the small number of blockchain adopters, binary measurement of adoption, and correlational design. This study provides initial bank-year panel evidence on blockchain adoption and financial reporting quality in Indonesian conventional banks. It extends Agency Theory by explaining how blockchain transparency may reduce managerial discretion and highlights that blockchain investment should currently focus on operational efficiency and transaction transparency rather than assumed reporting-quality improvements.